Pengaruh Penerapan E-Filing Dan E-Billing Terhadap Kepatuhan Wajib Pajak Orang Pribadi Dengan Pemahaman Perpajakan Dan Preferensi Risiko Wajib Pajak Sebagai Variabel Moderating (Studi Kasus Pada Kpp Pratama Surabaya Sawahan) - Novimilldwiningrum, Helena; Hidajat, Sjarief (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the effect of the implementation of E-filing and E-billing on Individual Taxpayer Compliance with Tax Understanding and Taxpayer Risk Preferences as Moderating Variables (Case Study at KPP Pratama Surabaya Sawahan). The population in this study were all individual taxpayers registered at KPP Pratama Surabaya Sawahan in 2020, which were 96,380 people. The sampling technique used is the non-probability sampling method, convenience sampling technique, with a total sample of 399 samples which are the number of effective individual taxpayers and non-effective individual taxpayers. because this research focuses on effective individual taxpayers. Data collection techniques using closed questionnaires. The data analysis technique in this study uses moderated regression analysis (MRA). The results showed that the implementation of e-filing and e-billing had a positive effect on Individual Taxpayer Compliance (Sig. 0.000 < 0.05). And understanding of taxation as a moderating variable strengthens the relationship between the application of e-filing and e-billing to individual taxpayer compliance with a negative coefficient with Sig. 0.000 < 0.05. And Risk Preference as a moderating variable strengthens the relationship between the implementation of e-filing and e-billing on Individual Taxpayer Compliance with a positive coefficient direction with Sig. 0.000 < 0.05.Â Â